Development and Validation of UV Spectrophotometric Method for Estimation of Tea Tree Oil in Bulk and Cosmeceutical Creams - Manjula, Basappa Palur; Joshi, Vijaya Gopalachar; Setty, Ramachandra Setty Siddam; Geetha, Muniyappa (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Tea tree oil, also known as Melaleuca alternifolia essential oil is widely used in skin care cosmeceuticals for its antibacterial, antifungal, analgesic and anti-inflammatory effect. The complex and variable composition of the oil poses many challenges to the analytical chemist and a recent survey of analytical methods indicated only a few simple and validated methods for estimation of the oil. Aim: A quality by design approach has therefore been adopted to develop a simple and novel UV spectrophotometric method for estimation of tea tree oil in bulk and cosmeceutical creams. Materials and Methods: UV spectrophotometric method was developed for estimation of Tea tree oil using dichloromethane- methanol (54 % v/v) solvent system. The method was then validated under optimized conditions for accuracy, precision and ruggedness, limit of detection and limit of quantification as per ICH: Q2 (R1) guidelines. Results: A characteristic spectral peak was observed at 267 nm and linearity was established over a concentration range of 10-160 mcg/ml with R2 value of 0.9961. Accuracy based on recovery studies, 100.5-113.6 %, precision and ruggedness based on % RSD values less than 2 %, LOD, 0.1277mcg/ml and LOQ and 4.195 mcg/ml indicated that the method is sensitive enough to be used for routine estimation. Conclusion: The method is robust and has been used to determine the essential oil content of two cosmeceutical creams.
Keywords: Tea tree oil; UV spectrophotometry; Box Behnken design; Optimization; Routine determination; Cosmeceutical cream